Design and development of a supported tiered software for teaching and learning using a connected mobile learning application - Sim, Tze Ying *; Lau, Sian Lun *; Zipf, P.; Kimm, K. (IDOSI Publications, 2014)
Since the last decade, one of the fastest growing technologies is the mobile technology [1]. Mobile technology, which ranges from mobile phones, portable gaming devices to tablet computers, is getting affordable in recent years. Mobile learning should not be viewed as just a technology that provides E-Learning on mobile devices. Classic mode of mobile learning focuses in content delivery but the trend is to extend learning with the capabilities of communication and interaction as well as content capture and transfer [3]. In this paper, a discussion based on the experience of the authors in designing a mobile learning platform prototype using interconnected mobile devices and server infrastructure is presented. The prototype allows a lecturer to teach using a tablet while students learn and interact with the lecturer using their own devices. A preliminary result based on students’ feedback is used to prioritize and improve the features.